2009 and beyond: the decade of personalised medicine. (23rd December 2008) - Du, Pan; Lin, Simon M.; Yang, Mary Qu; Yang, Jack Y.
With a better understanding of the human genome, it is possible to tailor the medical care, including prevention, diagnosis and treatment of disease, to an individual's needs. This revolution of medical care is called Personalised Medicine. This paper provides a brief review of recent progresses in high-throughput measurement technologies, their effects on personalise medicine, milestone projects in human genome researches and related challenges in bioinformatics and computational biology.